Ferroelectric ceramic/polymer composite for measuring X-ray intensity in the ortovoltage range - Sakamoto, W. K. [UNESP]; Estevam, Giuliano Pierre; de Carvalho, Aparecido Augusto; Pontes, Wesley; de Paula, M. H. (IEEE, 2007)
Pyroelectric sensors work as a thermal transducer converting the non-quantified thermal flux into the output measurable quantity of electrical charge, voltage or current. Ferroelectric ceramics and ferroelectric polymers have been extensively used as thermal detectors. More recently the research in the field of pyroelectricity has been concentrated on discovering materials with higher figures of merit (FOM), which means better sensing materials. Composite materials obtained with ferroelectric ceramics embedded in polymer host have received great attention because of their formability, mechanical resistance and the possibility to change their dielectric property varying the volume fraction of ceramic particles. In this work composite films made of modified lead titanate (PZ34) and poly(ether-ether-ketone) (PEEK) were characterized and used as sensing element to measure X-ray intensity in the ortovoltage range (120 - 300 kVp). The sensor response varies from 2.70 V to 0.80 V in the energy fluency range of 6.30 to 37.20 W/m(2). Furthermore the absorbed energy was analyzed as a function of the ionizing energy. The results indicate that the PZ34/PEEK composite with 60/40 vol.% can be useful to monitor X-ray radiation therapy.